Theoretical Approach to Agroturism and Its Contribution to Local Development - Lisbet Eunice Pérez Anzardo; Evelina Cardet Fernández; Irina Reyes Martínez; Reynaldo Guzmán Páez (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2021)
Tourism as a driver of local development. It is also an international practice with results exhibited by countries from various latitudes. Therefore, a tourist management is imposed who allows the identification of gaps in tourist competitiveness, customer satisfaction, increased income, and an improvement in the quality of the population life. Today, city dwellers appreciate the rural world as the corner where tranquility, authenticity, nature, traditions, among other riches, are treasured. This new concept of rural tourism makes it possible for the great tourist currents to seek other spaces that are not only sun and beach destinations, as well as representing an attractive alternative for tourists. The following article makes a reflection on the basis of the main concepts and trends linked to agrotourism as local development strategies in order to facilitate the correct management of this tourism modality. Hence, theoretical methods were used such as analysis and synthesis, historical-logical, systemic structural; and empirical ones such as scientific observation, interview, study of normative documents, among others. As a result, the bases were laid for the theoretical-practical deepening of the research and a group of conditions are proposed that allow rural tourism to develop as an outstanding framework of the agricultural sector, and diversify the offer so that it behaves as a decisive factor in local development. The study has been validated and presented at national and international scientific events with positive results.